2023
DOI: 10.1111/vsu.13944
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting prognosis in canine subcutaneous mast cell tumors: 45 cases

Abstract: Objective: To evaluate the clinical outcome of subcutaneous mast cell tumors (SQMCT) and to identify clinical and histological characteristics of more aggressive disease. Study design: Retrospective study. Animals: Forty-five dogs with 48 SQMCTs. Methods: Medical records were reviewed (2011-2021) for patient information, clinical, and histopathological data including multinucleation, necrosis, invasion into local muscle, an infiltrative growth pattern, tumor grade (if listed), mitotic index, and surgical margi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Mast cell infiltration in tumours has recently been reported [ 27 , 28 ]; unfortunately, the phenotypic characteristics of mast cells and their functions are still poorly understood. Many immune coinhibitory signals are associated with immunosuppression in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cell infiltration in tumours has recently been reported [ 27 , 28 ]; unfortunately, the phenotypic characteristics of mast cells and their functions are still poorly understood. Many immune coinhibitory signals are associated with immunosuppression in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…a more recent study, Gill et al examined if the Kiupel and a modified Patnaik grading scheme (excluding "depth of invasion") could be applied to prognosticate subcutaneous MCTs, however, due to the low number of high-grade tumors no conclusion could be drawn. The most recent study by Cherzan et al 42 demonstrated that histologic parameters used in grading cutaneous MCTs such as multinucleation, infiltrative growth pattern, or mitotic count were also prognostic in a subset of more aggressive subcutaneous MCTs. Oral mucous membrane MCTs are more likely to behave aggressively with frequent lymph node metastasis and locoregional recurrences, especially when exhibiting features of high-grade tumors such as a high mitotic index.…”
Section: Discussionmentioning
confidence: 99%
“…examined if the Kiupel and a modified Patnaik grading scheme (excluding “depth of invasion”) could be applied to prognosticate subcutaneous MCTs, however, due to the low number of high‐grade tumors no conclusion could be drawn. The most recent study by Cherzan et al 42 . demonstrated that histologic parameters used in grading cutaneous MCTs such as multinucleation, infiltrative growth pattern, or mitotic count were also prognostic in a subset of more aggressive subcutaneous MCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, in terms of prognosis, it was believed that the majority of scMCTs exhibited a favorable prognosis compared to cMCTs, with extended survival times and low metastatic rates and recurrence rates (4% and 8%, respectively) [7]. Later studies solely focusing on scMCTs, however, reported that a larger proportion of the scMCT cases might exhibit an aggressive biologic behavior [10,[12][13][14]. Our study aimed to describe signalment of dogs and histopathological features of scMCTs and cMCTs across a large dataset of canine MCTs of the skin.…”
Section: Introductionmentioning
confidence: 99%